The Role of Peers in Shaping Sanguine Personality in Islamic Guidance and Counseling Students at STAI Al Furqan Makassar - Alda Alda; Ismail Ismail; Fita Dewi Yuniar; Rosika Indri Karadona (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This research aims to examine how interactions and the role of peers contribute to the formation of sanguine personality among students of the Islamic Guidance and Counseling Study Program at STAI Al Furqan Makassar. The college years are a challenging transitional phase, where social interactions, especially with peers, play a crucial role in character formation and the development of students' social skills. The sanguine personality, characterized by cheerful, expressive, and sociable traits, is considered highly relevant to the demands of the profession as an Islamic counselor. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation involving nine students from the 4th and 6th semesters. The research results show that intensive interaction and emotional support from peers can encourage students to be more open, confident, and communicative. In addition, the role of peers also serves as a stimulus in the formation of positive and adaptive character that supports students' readiness as prospective educators in the community. These findings emphasize the importance of creating a supportive social environment on campus to foster balanced personality development.